Lamotrigine compared to placebo and other agents with antidepressant activity in patients with unipolar and bipolar depression: a comprehensive meta-analysis of efficacy and safety outcomes in short-term trials. (30th September 2016) - Solmi, Marco; Veronese, Nicola; Zaninotto, Leonardo; van der Loos, Marc L. M.; Gao, Keming; Schaffer, Ayal; Reis, Catherine; Normann, Claus; Anghelescu, Ion-George; Correll, Christoph U.
Abstract : Objectives: To meta-analytically summarize lamotrigine's effectiveness and safety in unipolar and bipolar depression. Methods: We conducted systematic PubMed and SCOPUS reviews (last search =10/01/2015) of randomized controlled trials comparing lamotrigine to placebo or other agents with antidepressant activity in unipolar or bipolar depression. We performed a random-effects meta-analysis of depression ratings, response, remission, and adverse effects calculating standardized mean difference (SMD) and risk ratio (RR) ±95% confidence intervals (CIs). Results: Eighteen studies (n=2152, duration=9.83 weeks) in patients with unipolar depression (studies=4, n=187; monotherapy vs lithium=1, augmentation of antidepressants vs placebo=3) or bipolar depression (studies=14, n=1965; monotherapy vs placebo=5, monotherapy vs lithium or olanzapine+fluoxetine=2, augmentation of antidepressants vs placebo=1, augmentation of mood stabilizers vs placebo=3, augmentation of mood stabilizers vs trancylpromine, citalopram, or inositol=3) were meta-analyzed. Lamotrigine's efficacy for depressive symptoms did not differ significantly in monotherapy vs augmentation studies (vs. placebo: p=0.98, I 2 =0%; vs active agents: p=0.48, I 2 =0%) or in unipolar vs bipolar patients (vs placebo: p=0.60, I 2 =0%), allowing pooling of each placebo-controlled and active-controlled trials. Lamotrigine outperformed placebo regarding depressive symptoms (studies=11, n=713 vs n=696; SMD=–0.15, 95% CI=–0.27, –0.02, p=0.02, heterogeneity: p=0.24) and response (after removing one extreme outlier; RR=1.42, 95% CI=1.13–1.78; p=0.003, heterogeneity: p=0.08). Conversely, lamotrigine did not differ regarding efficacy on depressive symptoms, response, or remission from lithium, olanzapine+fluoxetine, citalopram, or inositol (studies=6, n=306 vs n=318, p-values=0.85–0.92). Adverse effects and all-cause/specific-cause discontinuation were similar across all comparisons. Conclusions: Lamotrigine was superior to placebo in improving unipolar and bipolar depressive symptoms, without causing more frequent adverse effects/discontinuations. Lamotrigine did not differ from lithium, olanzapine+fluoxetine, citalopram, or inositol.